From the Field -- Dr. Jack A. Nelson: Early Pioneer of Media and Disabilities - Jensen, Matt (Disability Studies Quarterly, 2002)
This personal profile was written because of the critical innovative surge Nelson made in a field that at the time was almost non-existent. His awards as a writer, both academic and professional, show his consistent concern for those in the field of disabilities. As a paraplegic, Nelson is an example for people with disabilities doing continuous research to understand the disabled person's role in the media and how technology offers them a "new world" which they can enter. Though he is retired, Nelson is still known for his concern for people with disabilities. Essentially, this paper gives recognition to a man who promoted a field of research that was in the nascent stages.